Calculation method for surface depletion depth of metallic bonding phase

JP7652427B2Active Publication Date: 2025-03-27KYUSHU MIZUHO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022066419
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-04-13
Publication Date
2025-03-27
Estimated Expiration
2042-04-13

Smart Images

  • Figure 0007652427000003
    Figure 0007652427000003
  • Figure 0007652427000004
    Figure 0007652427000004
  • Figure 0007652427000005
    Figure 0007652427000005
Patent Text Reader

Abstract

To provide a method for calculating the surface depletion depth of a metal bonding phase, which enables the corrosion depth to be accurately calculated in a non-destructive manner by efficiently calculating the amount of the metal bonding phase which smoothly changes at the interface by allowing the metal bonding phase to slightly remain between hard particles in a deficient layer after selective corrosion.SOLUTION: A depletion depth of a metal bonding phase is calculated from four pieces of information, i.e., a composition of a cemented carbide matrix, a composition measured by characteristic X-ray analysis from the upper surface after the cemented carbide matrix is processed into a tool and the metal bonding phase is selectively corroded, a composition of the metal bonding phase slightly remaining between hard particles in the depletion region of the selectively corroded metal bonding phase, and an analysis depth measured by the emission of the characteristic X-ray in the characteristic X-ray analysis.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for calculating the surface depletion depth of a metallic binder phase when selectively corroding only the metallic binder phase on the surface of a cemented carbide, out of the hard particle phase and metallic binder phase contained in the cemented carbide constituting a cemented carbide tool. [Background technology]

[0002] In recent years, Patent Document 1 has reported that the properties of cemented carbide tools used as cutting tools can be improved by removing the metallic binder phase from the tool surface and leaving only the hard particle phase on the surface of the cemented carbide alloy, which is composed of a hard particle phase and a metallic binder phase.

[0003] The metallic bonding phase is removed by chemical etching or physical etching. For example, Patent Document 2 discloses a process for removing the surface metallic bonding phase using aqua regia or nitric acid solution. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2019 / 065677 publication [Patent Document 2] JP 2019-206754 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, it is known that when the metallic bonding phase is selectively removed by chemical etching or physical etching, the surface has improved wear resistance, voltage resistance, lubricity, etc. in a specific usage environment. However, when the metallic bonding phase of a cemented carbide having a high ratio of hard particle phase is removed from the surface by etching, the metallic bonding phase is selectively corroded in a tunnel shape, leaving the hard particle phase in a mesh shape.

[0006] Figure 1(a) is an image of the surface before corrosion taken with a scanning electron microscope, and Figure 1(b) shows the hard particles 1 and metallic bonding phase 2 on the surface after corrosion. Even when measuring with a stylus-type surface roughness tester, there is a limit to the responsiveness of the probe when it descends through gaps between hard particles on the order of several μm, and it is virtually impossible to accurately measure the depth of corrosion that has penetrated deep into the mesh-like structure.

[0007] Figure 2 is a schematic representation of the cross-section of such corrosion. Of the hard particles 1 and metallic bond phase 2 contained in the cemented carbide that constitutes the cemented carbide tool, only the metallic bond phase 2 is selectively corroded. Figure 2 shows a smooth surface 3 after polishing and a surface 4 after selective corrosion of the metallic bond phase 2, with metallic bond phase 5 remaining in the hard particle adhesion area.

[0008] One of the few methods for measuring such corrosion depth is to observe cross-sectional samples prepared using an ion beam; however, this is a destructive test of the product, and considering the measurement time and cost, it is not suitable for quality assurance of mass-produced products.

[0009] Even when analytical equipment attached to an electron microscope or X-ray measuring equipment is used to measure the depth of the vacancies, it is very difficult to quantitatively express the amount of the metallic bonding phase, which changes gradually at the interface.

[0010] The present invention has been made in consideration of the above circumstances, and aims to provide a method for calculating the surface depletion depth of a metallic bonding phase, which makes it possible to efficiently calculate the amount of metallic bonding phase that changes smoothly at the interface due to the small amount of metallic bonding phase remaining between hard particles in the depletion layer after selective corrosion, and to accurately calculate the corrosion depth in a non-destructive manner. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention provides a method for calculating the surface depletion depth of a metallic bonding phase, which is characterized by calculating the depletion depth of the metallic bonding phase by characteristic X-ray analysis when selectively corroding only the metallic bonding phase on the surface of a cemented carbide among the hard particle phase and metallic bonding phase contained in the cemented carbide constituting a cemented carbide tool.

[0012] In addition, in the present invention, the depletion depth of the metallic bonding phase in the selective corrosion can be calculated from four pieces of information: the composition of the cemented carbide base body, the composition measured by characteristic X-ray analysis from the top surface after the cemented carbide base body is processed into a tool and the metallic bonding phase is selectively etched, the composition of the metallic bonding phase remaining slightly between the hard particles in the depleted region of the selectively etched metallic bonding phase, and the analysis depth measured by the emission of characteristic X-rays in the characteristic X-ray analysis.

[0013] As a result, in the depletion zone after selective corrosion, a small amount of metallic bonding phase remains between the hard particles, and it becomes possible to efficiently calculate the amount of metallic bonding phase that changes smoothly at the interface, and to accurately calculate the corrosion depth in a non-destructive manner. Note that, from the viewpoint of strength retention, the selective corrosion depth is premised on being approximately the same as the average grain size of the hard particles. Effect of the Invention

[0014] According to the present invention, a method for calculating the surface depletion depth of a metallic bonding phase can be realized, which makes it possible to efficiently calculate the amount of metallic bonding phase that changes smoothly at the interface by virtue of the small amount of metallic bonding phase remaining between the hard particles in the depletion layer after selective corrosion, and to accurately calculate the corrosion depth in a non-destructive manner. [Brief description of the drawings]

[0015] [Figure 1] This is a scanning electron microscope image of the surface showing the progression of selective corrosion. [Diagram 2] FIG. 2 is a schematic diagram of a cross section after selective corrosion. [Diagram 3]FIG. 1 is a schematic diagram showing a cross section of a cemented carbide tool after selective etching of the metallic bonding phase, and the change in the amount of CO, which is the main component of the metallic bonding phase, during the selective etching. [Figure 4] FIG. 2 is a diagram for defining the depletion depth of a metallic bonding phase. [Diagram 5] 1 is a flow chart of a method for measuring the depletion depth of a surface metal binder phase in a cemented carbide. [Figure 6] 13 is a flowchart for calculating a defect depth. [Figure 7] FIG. 13 is a diagram showing a comparison between calculated and measured depletion depths for fine grains. [Figure 8] FIG. 13 is a diagram showing a comparison between calculated and measured deficiency depths for medium grains. [Figure 9] FIG. 13 is a diagram showing a comparison between calculated and measured depletion depths for coarse grains. [Figure 10] FIG. 1 is a diagram showing the deficiency depth of fine grains actually measured by SEM observation. [Figure 11] FIG. 1 is a diagram showing the deficiency depth of medium grains measured by SEM observation. [Figure 12] FIG. 1 is a diagram showing the deficiency depth of coarse grains actually measured by SEM observation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a method for calculating the surface depletion depth of a metallic bond phase according to the present invention will be described based on an embodiment thereof.

[0017] The present invention calculates the depletion depth of the metallic bonding phase by characteristic X-ray analysis when selectively corroding only the metallic bonding phase on the surface of the cemented carbide among the hard particle phase and metallic bonding phase contained in the cemented carbide constituting the cemented carbide tool. More specifically, the depletion depth of the metallic bonding phase is calculated from four pieces of information: the composition of the cemented carbide base body, the composition measured by characteristic X-ray analysis from the top surface after the cemented carbide base body is processed into a tool and the metallic bonding phase is selectively corroded, the composition of the metallic bonding phase remaining in small amounts between the hard particles in the depleted region of the selectively corroded metallic bonding phase, and the analysis depth measured by the emission of characteristic X-rays in the characteristic X-ray analysis.

[0018] Figure 3 shows the cross section of the metallic bonding phase on the surface of a cemented carbide tool after selective etching and the C, the main component of the metallic bonding phase, O The graph shows the change in the amount of C in the depleted zone after selective corrosion. O The amount of C does not become completely zero, but fluctuates. From the area where the metallic bonding phase has been removed by corrosion, the amount of C in the unreacted area changes gradually. O A transition in quantity is occurring and the depletion depth needs to be defined in this region.

[0019] Therefore, the inventors assumed a linear change in composition as shown in FIG. 4 and defined the depletion depth of the metallic bonding phase. O The amount is m1, and the small amount of C remaining between the hard particles O Assume that the amount is m2, m2 and m1 are constant values, and the transition from m2 to m1 is a linear change, as shown in FIG.

[0020] This linear change occurs at C O The transition position of the amount of Co is defined as the depletion depth d of the metallic bonding phase. Using these definitions, the analysis depth D measured by the X-rays irradiated in the characteristic X-ray analysis, and the amount of Co mx actually measured by the characteristic X-ray analysis, an equation is created based on the conservation of mass of the amount of Co, and the following equation (1) is obtained.

[0021]

number

[0022] By solving equation (1) with respect to the depletion depth d, we obtain equation (2).

[0023]

number

[0024] Here, the concentration of the metallic bonding phase remaining between the hard particles must be estimated in advance using an analysis method attached to the scanning electron microscope, etc. The analysis depth is determined by the X-ray intensity of the characteristic X-ray analyzer used and the composition of the cemented carbide to be analyzed.

[0025] Characteristic X-ray analyzers include energy dispersive X-ray analyzers (EDS) and wavelength dispersive X-ray analyzers (WDS). Both instruments measure the chemical composition of a sample by detecting the characteristic X-rays emitted from the sample surface, with EDS measuring the energy of the characteristic X-rays and WDS measuring the wavelength of the characteristic X-rays.

[0026] In the EDS, the reaction region of the characteristic X-rays is relatively shallow at a depth of several μm, whereas the WDS has an analysis depth of more than 10 μm. In the present invention, considering that the material to be analyzed has hard particles with a diameter of about several μm, it can be said that a wavelength dispersive characteristic X-ray analyzer (WDS), which can measure the depth of multiple particles, is a more desirable analytical device.

[0027] Although the impoverishment depth has such a simplified definition, it is arithmetically uniquely determined and always intersects with the transition region of the Co amount, so it is a very easy definition to handle when stating it as a rule in specifications, etc. In addition, because this measurement method is non-destructive, it can be used directly for shipping inspection and can also be used for cause analysis when an abnormality occurs.

[0028] FIG. 5 shows a flow chart of the above-described method for measuring the depletion depth of the surface metallic binder phase in a cemented carbide. As described above, it is possible to calculate the depletion depth d of the metallic binder phase from four pieces of information: the composition m1 of the cemented carbide matrix, the composition mx measured from the top surface by characteristic X-ray analysis after processing the same matrix into a tool and selectively etching the metallic binder phase, the composition m2 of the metallic binder phase remaining slightly between the hard particles in the depleted region of the selectively etched metallic binder phase, and the analysis depth D measured by the emission of characteristic X-rays in characteristic X-ray analysis. The corrosion depth obtained in this way can nondestructively and uniquely define the depth of the corrosion front, the boundary of which is ambiguous in reality.

[0029] The following describes the test content and results of the comparison of the calculated value and the measured value for the depletion depth d of the metallic bonding phase. FIG. 6 shows a flow chart for calculating the defect depth. Here, three types of materials with different particle sizes (fine grain, medium grain, and coarse grain) are targeted, with the average particle size of each being 0.6 to 1.0 μm for fine grains, 2.0 to 4.0 μm for medium grains, and 5.0 μm or more for coarse grains.

[0030] Samples are prepared for each of the fine, medium, and coarse grains, and the samples before etching are subjected to component analysis using a wavelength dispersive X-ray analyzer (WDS) and an energy dispersive X-ray analyzer (EDS) to identify the amount of metallic bond phase in the parent phase, which is used as the unprocessed calculation reference value.

[0031] The sample is then etched, and the components of the etched sample are analyzed to identify the amount of metallic bonding phase after etching. The cross section of the processed sample is processed by ion beam milling, and the depth of the metallic bonding phase deficiency is measured by SEM, and the analysis depth D for WDS and EDS is calculated for each of fine, medium, and coarse grains.

[0032] The depth of the metal bonding phase depletion was measured by SEM and the average depth was 0.14μm for fine grains, 0.85μm for medium grains, and 1.29μm for coarse grains. The depletion depth was measured at several locations and the average value was used. The treatment solution concentration was 10.0wt%, and the treatment time was 60 seconds for fine grains, 60 seconds for medium grains, and 100 seconds for coarse grains.

[0033] Based on this, the analysis depth D obtained was 4.0 μm for WDS and 0.6 μm for EDS for fine grains, 6.0 μm for WDS and 1.6 μm for EDS for medium grains, and 6.5 μm for WDS and 2.8 μm for EDS for coarse grains. Based on this analysis depth D, a formula for calculating the depletion depth d of the metallic bonding phase for each of fine, medium, and coarse grains is determined.

[0034] For samples not used in determining the analysis depth D described above, the metallic bonding phase depletion depth d is calculated by WDS analysis and EDS analysis, and the cross section of the sample not used in determining the analysis depth D is processed by ion beam milling, and the depth at which the metallic bonding phase is depleted is actually measured by SEM. The calculated value obtained in this way was compared with the actual measured value.

[0035] Next, a comparison between the deficiency depth d calculated using the analysis depth D determined by the method shown in the flow chart in FIG. 6 and the actual measured value will be described. Figures 7 to 9 show a comparison between the calculated and measured values ​​of the depletion depth d. Figure 7(a) shows the results of WDS for fine grains, and Figure 7(b) shows the results of EDS for fine grains. Figure 8(a) shows the results of WDS for medium grains, and Figure 8(b) shows the results of EDS for medium grains. Figure 9(a) shows the results of WDS for coarse grains, and Figure 9(b) shows the results of EDS for coarse grains. Note that the treatment depth in Figures 7 to 9 is the same as the depletion depth.

[0036] The calculated depletion depths for fine grains were 0.14 μm for WDS and 0.12 μm for EDS, for medium grains were 0.71 μm for WDS and 0.68 μm for EDS, and for coarse grains were 1.32 μm for WDS and 1.31 μm for EDS.

[0037] On the other hand, the average value of the measured depletion depth was 0.12 μm for fine grains, 0.79 μm for medium grains, and 1.24 μm for coarse grains. The average value of the measured depletion depth was obtained by processing the cross section of the sample by ion beam milling, and measuring the depth of the depletion of the metallic bonding phase at several points using SEM. Figure 10 is a diagram showing the actual measurement of the depletion depth for fine grains using SEM. Figure 11 is a diagram showing the actual measurement of the depletion depth for medium grains using SEM. Figure 12 is a diagram showing the actual measurement of the depletion depth for coarse grains using SEM. As a result of the measurement, the difference between the calculated value and the actual measurement value for fine grains was 0.02 μm for WDS and 0.00 μm for EDS, for medium grains, 0.08 μm for WDS and 0.11 μm for EDS, and for coarse grains, 0.08 μm for WDS and 0.07 μm for EDS.

[0038] The evaluation of the difference between the calculated and measured deficiency depths will be described below. The difference between the calculated and measured depletion depths is less than half the particle diameter of the hard particles for all the fine, medium and coarse grains. The value of half the particle diameter of the hard particles can be recognized as a boundary value that determines whether the hard particles fall off or not, and if the difference between the calculated and measured depletion depths exceeds half the particle diameter of the hard particles, it will have a negative effect on the function of the cemented carbide tool when performing selective corrosion. However, according to the test results, the difference between the calculated depletion depth and the measured value is much smaller than half the particle diameter of the hard particles, so it was confirmed that the calculation method of the depletion depth according to the present invention is extremely effective. [Industrial Applicability]

[0039] The present invention can be widely used in the field of machining of cemented carbide tools as a method for calculating the surface depletion depth of a metallic bonding phase, which makes it possible to efficiently calculate the amount of metallic bonding phase that changes gradually at the interface due to the small amount of metallic bonding phase remaining between the hard particles in the depletion layer after selective corrosion, and to accurately calculate the corrosion depth in a non-destructive manner. [Explanation of symbols]

[0040] 1 hard particles 2 Metallic bonded phase 3 Smooth surface after polishing 4. Surface after selective etching of metal bonding phase 5 Metallic bonding phase remaining in the hard particle adhesion area

Claims

[Claim 1] A method for calculating a surface depletion depth of a metallic bonding phase, the method comprising the steps of: selectively corroding only the metallic bonding phase on the surface of a cemented carbide of a cemented carbide tool by using a characteristic X-ray analysis to calculate the depletion depth of the metallic bonding phase, the method comprising the steps of: The method for calculating the surface depletion depth of the metallic bonding phase in the selective corrosion is characterized in that the depletion depth of the metallic bonding phase in the selective corrosion is calculated from four pieces of information: a composition of a cemented carbide base, a composition measured by characteristic X-ray analysis from the top surface after the cemented carbide base is processed into a tool and the metallic bonding phase is selectively etched, a composition of the metallic bonding phase remaining slightly between hard particles in a depleted region of the selectively etched metallic bonding phase, and an analysis depth measured by emission of characteristic X-rays in the characteristic X-ray analysis.

Citation Information

Patent Citations

  • Method for analyzing noticed element in sample by electron ray irradiation

    JP1987050648A

  • Manufacturing method of slide component

    JP2019206754A

  • Cutting tool and manufacturing method therefor

    WO2019065677A1